Teacher's Perception of Early Writing as a Readiness Skill in Kindergarten - Yuantini, Gustiana; Suryani, Yuni Dwi (PIAUD Universitas Islam Negeri Sunan Kudus, 2022)
Early writing readiness is one of the basic abilities needed in preparation for elementary school. This study aims to obtain the perceptions of teachers regarding early writing readiness in kindergarten. This research was conducted through a survey to support the development of learning media products with a sample of 26 kindergarten teachers in Rengas Village. The results showed that most teachers used the assignment method of 38.4%, the lecture method of 34.6% the demonstration method of 23.1%. Then the greatest percentage of 42.3% is the perception of teachers using children's worksheet media, and also the largest percentage of teachers' perceptions using writing learning resources in the form of pencils or crayons by 50%, An analysis of learning activities at the beginning of class writing it is known that the largest percentage of 61.5% of activities carried out by playing. Based on the results of the survey above, the researcher saw that optimization of children's writing skills was still needed by the way the teacher made preparations including the selection of strategies, methods, and learning media to be used. Writing activities carried out in a fun way not only make children skilled in writing, but children will be interested and happy while writing.